2020
DOI: 10.1088/2515-7639/ab854a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hexagonal boron nitride 2D layers using polymer derived ceramics route and derivatives

Abstract: Hexagonal boron nitride (h-BN) is nowadays an increasingly attractive material, especially for two-dimensional material applications, due to its intrisic properties. However, its properties are highly dependent on the used synthesis approach. The polymer derived ceramics (PDCs) route allows elaboration of h-BN with tailored textural and structural properties. Here, we demonstrate the interest of the PDCs pathway for the synthesis of h-BN. Growth of h-BN single crystals with crystal sizes of a few microns at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…From the surface profile plot, the interplanar distance (d) is found to be ∼0.33 nm, which indicates the (002) plane of the h-BN phase. 20,21 Thus, the coexistence of h-BN and g-C 3 N 4 nanodomains is consistent with the aforementioned XRD results, suggesting the novelty of synthesized B x C y N z nanosheets. Because it is already reported that h-BN is a layered material, 22 the d spacing calculated from the HRTEM image actually represents the interlayer spacing, which should be in the nanometer range although the reported diffraction peak of h-BN is sharp enough.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…From the surface profile plot, the interplanar distance (d) is found to be ∼0.33 nm, which indicates the (002) plane of the h-BN phase. 20,21 Thus, the coexistence of h-BN and g-C 3 N 4 nanodomains is consistent with the aforementioned XRD results, suggesting the novelty of synthesized B x C y N z nanosheets. Because it is already reported that h-BN is a layered material, 22 the d spacing calculated from the HRTEM image actually represents the interlayer spacing, which should be in the nanometer range although the reported diffraction peak of h-BN is sharp enough.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Prior to the exfoliation, the substrates were cleaned using acetone for 5 min, isopropyl alcohol for 5 min, followed by 5 min of 30 W oxygen plasma treatment. Two control samples grown at atmospheric pressure have also been used: a APHT (atmospheric pressure, high temperature) sample grown in KSU (Kansas, USA) using Ni/Cr solvent 34 , and a sample grown in LMI (Lyon, France) using PDC (polymer derived ceramics) 35 . Both samples have been exfoliated using adhesive tape on a SiO 2 /Si substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Following pioneering studies [16][17][18], we have recently proposed an alternative synthesis approach conducted under quite soft conditions, involving a polymer derived ceramics (PDC) route and a post-sintering process performed into a pressurecontrolled furnace (PDC/pressure-controlled sintering (PCS)) [19]. With this original coupling, large and transparent hBN single crystals up to millimeter size have been obtained through softer conditions and have led to boron nitride nanosheets (BNNSs) presenting a lateral size up to few hundreds microns after exfoliation.…”
Section: Introductionmentioning
confidence: 99%